Developments in Managing and Exploiting Risk. - Abrahamsen, Eirik B.; Engemann, Kurt J. (Developments in Managing and Exploiting Risk ;, 2020)
Within the area of safety, different perspectives exist on how to provide an adequate basis for managing risk. Safety experts emphasize the cautionary principle, stating that in the face of uncertainty, caution should be the dominant standard. On the other hand, relying on economic assessment often leads to decisions made using expected values to optimize return on investment. Safety Risk Management: Integrating Economic and Safety Perspectives aims to illuminate this dichotomy while debating important questions. For example, is 'safety always first?' Additionally, in many risk environments only partial knowledge is available and limited emphasis may be mistakenly given to uncertainty. Risk management deals with balancing the dilemma inherent in exploring opportunities on the one hand, and avoiding losses, accidents, and disasters, on the other. Safety Risk Management: Integrating Economic and Safety Perspectives comprises a collection of work in this field with special focus given to situations with the potential for substantial reward but also with the possibility of immense losses and extreme consequences. This book aims to contribute to clarifying the problem by proposing an appropriate basis for managing risk to meet related practical challenges. The book consists of two parts: chapters covering fundamental concepts and approaches; and, chapters illustrating applications of these fundamental principles.